Opportunities for development of social work in Czech schools - Matulayova, Tatiana; Pešatová, Ilona; Michalova, Zdenka (Wydawnictwo Uniwersytetu Rzeszowskiego, 2015)
Analysis of the relevant Czech legislation in the area of education system demonstrates that there are no legislative prerequisites for establishing the position of school social worker (Pešatová, Matulayová 2013). At present, there are no institutions of tertiary education system in the Czech Republic which would prepare and train the social workers for being a specialist in the school environment. There are social workers employed in the school sector, yet their job description covers administration rather than assistance provided in a professional manner. It can be concluded, that the profession of school social work is unrecognised in this system. There are several causes of the current state which appears unsatisfactory from the perspective of social work. One of them is the fact that the counselling system at schools was built in the 1970’s. Those days, due to ideology, social work was no longer institutionalised as a profession in the Czech society. Thus, the counselling system was built as a space for providing services of specialised pedagogical and psychological profession.
Keywords: social work; education; disabled pupils; pupils with problems